IDENTIFIKASI SPESIES ORCHIDACEAE DI BLOK KOLEKSI TAMAN HUTAN RAYA WAN ABDUL RACHMAN LAMPUNG, INDONESIA - Ambarwati Ambarwati; Indriyanto Indriyanto; Yusnita Yusnita (Lambung Mangkurat University-Indonesia, 2019)
Wan Abdul Rachman Forest Park is a nature conservation area in Lampung Province, Indonesia, which is devided into five large blocks, one of which is the collection block for plants and animal. The function of this collection block is for area of plant and animal collection, protection, and conservation. One focus of interest of the plant collection and conservation in the collection block of this Forest Park is Orchidaceae, since this flowering plant family has large diversity. In the past, this collection block was park of the primary forest. Due to land clearing by the surrounding community, currently this area became a mixed forest. Therefore, a study of orchid identification in this block is needed to know the current and actual orchid diversity, density and distribution in this area. The research was conducted since March to April 2018 in area of 141,18 ha of the collection block. Using 2% of sampling intensity, data of orchid were collected by surveying the area using a line-plot method consisting a total of 70 plots. The results showed that there were a total of 29 epiphytic orchid plants identified as 8 species, namely Dendrobium subulatum, Dendrobium phalaenopsis, Dendrobium crumenatum, Adenoncos elongata, Liparis lacerata, Cymbidium finlaysonianum, Eria javanica, Thecostele alata, and 3 genera, namely Cymbidium sp., Coelogyne sp., and Cleisostoma sp. Those orchid species or genera were living on 7 species of host plants with density varied from 0.36 – 3.21 plants per ha. Orchid species with the highest densities were Dendrobium subulatum (3.6 plants/ha).